Gestión administrativa en el cyber Evans del cantón Alfredo Baquerizo Moreno - Cruz Alvear, Melany Paola (2022)
The subject is about the Administrative management in the Cyber Evans in the Alfredo Baquerizo Moreno canton, the same one that is developed with the purpose of analyzing the administrative management that is exercised in the activities of the Cyber Evans, for the development of the investigation the descriptive method that has as its function an approach related to the enhancement of research problems. This methodology is composed of qualitative and quantitative variables that group collections of information, using questionnaires from Surveys carried out on clients and Interviews with the owner and employee of the premises. It was found that there are factors with negative impacts on administrative management, not having an organizational structure, not having objectives to be carried out, directly affecting the administrative method developed. It is recommended to carry out a short-term analysis in the application of administrative processes, since in this way the changes can be measured, in order to determine if the expected results were obtained, all this will lead to improving the administration within the premises.